Impact of Multilevel Facetectomy and Rod Curvature on Anatomical Spinal Reconstruction in Thoracic Adolescent Idiopathic Scoliosis. Issue 19 (1st October 2018) - Sudo, Hideki; Abe, Yuichiro; Kokabu, Terufumi; Kuroki, Kei; Iwata, Akira; Iwasaki, Norimasa
Abstract : Study Design: A prospective, nonrandomized study. Objective: The aim of this study was to assess surgical outcomes of multilevel facetectomy and rod curvature with simultaneous double-rod rotation technique for anatomical spinal reconstruction in thoracic adolescent idiopathic scoliosis (AIS). Summary of Background Data: Although some surgical techniques maintain or restore thoracic kyphosis (TK), next-generation strategies for thoracic AIS should include corrections in three anatomical planes. Methods: The study included 39 consecutive patients with Lenke 1 or Lenke 2 thoracic AIS treated at our institution. After all-level facetectomy at instrumentation level, except for the lowest intervertebral segment, two rods were identically bent to guide postoperative anatomical TK without reference to the intraoperative coronal alignment of the AIS deformity. Outcome measures included patient demographics, radiographic measurements, and Scoliosis Research Society (SRS) questionnaire scores. Results: After 2 years of follow-up, the average main thoracic Cobb angle correction rate was 83.5%, and the final correction loss was 2.2°. The average preoperative TK (T5–T12) significantly increased from 13.2° to 24.6° ( P  < 0.001) at final follow-up. The percentage of patients with a T6–T8 location of the TK apex significantly increased from 51.3% preoperatively to 87.2% at final follow-up. The average preoperative vertebral rotation angle significantly decreased from 18.7° to 12.8° postoperatively ( P  < 0.001). The average preoperative total SRS questionnaire score significantly increased from 3.5 to 4.5 ( P  < 0.001) at final follow-up. There was no implant breakage and vascular and neurologic complications, with all patients demonstrating solid fusion at final follow-up. Conclusion: Multilevel facetectomy and rod curvature play an important role in anatomical spinal reconstruction in patients with thoracic AIS. From the spatiotemporal point of view, four-dimensional correction could be actively performed by rod curvature under multilevel facetectomy and is expected to obtain an anatomical thoracic spine postoperatively, indicating that an anatomically designed rod could be supplied as a pre-bent rod. Level of Evidence: 3